Desain Inovasi Pendidikan yang Berpihak Pada Peserta Didik dan Memerdekakan Peserta Didik Abad 21 - Mediana, Verga; Agustiani, Iis; H, Hetilaniar (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Ki Hadjar Dewantara, an Indonesian educational figure, is renowned for his holistic approach to education through the concept of "Taman Siswa." His educational philosophy emphasizes experiential learning, critical thinking, and moral development. According to Dewantara, liberating education not only imparts knowledge but also instills values of care and justice, which are crucial for building an inclusive society. Thus, this approach to education holds significant potential for advancing Indonesia and fostering a generation that is both caring and just.